1994
DOI: 10.1142/s0218625x94000564
|View full text |Cite
|
Sign up to set email alerts
|

THE GROWTH MODES AND STRUCTURES OF NO ON Ni{111}

Abstract: The growth modes of NO on Ni{111} have been determined using a novel LEED technique. Measurement of LEED intensities at the superstructure beam positions as a function of coverage indicate that initial adsorption occurs randomly up to a coverage of 0.25 ML. After this point islanding occurs until the c(4×2) half-monolayer coverage is reached. Diffuse LEED I(V) analysis has also been used to determined the structure of a low coverage phase. This low coverage phase gives rise to an optimum structure consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…In addition, recent studies on Ni{l 11} have thrown some doubts on band assignments for NO. 26,27 Figure lf,g show the results of heating the (NO)2 multilayer formed at 45 K. The multilayer can be seen to desorb between 57 and 63 K, in complete agreement with the 60 K multilayer desorption temperature reported elsewhere. 4 The band that is left after desorption of the multilayer is at 1863 cm-1.…”
Section: Methodssupporting
confidence: 84%
“…In addition, recent studies on Ni{l 11} have thrown some doubts on band assignments for NO. 26,27 Figure lf,g show the results of heating the (NO)2 multilayer formed at 45 K. The multilayer can be seen to desorb between 57 and 63 K, in complete agreement with the 60 K multilayer desorption temperature reported elsewhere. 4 The band that is left after desorption of the multilayer is at 1863 cm-1.…”
Section: Methodssupporting
confidence: 84%
“…For the adsorption of NO on Pt{110} assignments are based on the following band ranges: G1720 cm -1 , on top NO; 1600-1720 cm -1 , bridged NO; < 1600 cm -1 , 3-fold NO, which are fully consistent with all available data. We note that recent structural 15,16 and theoretical 19,20 studies show no evidence for bent NO species.…”
Section: Assignment Of Infrared Bands For Chemisorbed Nomentioning
confidence: 48%
“…There is some controversy about band assignments for NO adsorbed on surfaces, with NO adsorption on Ni{111} being a particularly good example. Here, it was originally concluded from infrared data that NO occupied different adsorption sites as a function of coverage, but photoelectron diffraction 15 and LEED 16 measurements showed that this was not the case. Infrared spectroscopic investigations showed two NO stretching bands: 1507 cm -1 at low coverage and 1581 cm -1 at 0.5 ML coverage.…”
Section: Assignment Of Infrared Bands For Chemisorbed Nomentioning
confidence: 97%
“…The first case demonstrating this was the adsorption of NO on Ni{111}, which was studied using a wide variety of techniques over the years. [29][30][31][32][33][34][43][44][45][46][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] The main controversy arose from the assignments of vibrational bands identified in a RAIRS study by Erley 29 and in an earlier EELS study by Ibach and co-workers. 30 In the RAIRS study, NO adsorption on Ni{111} was studied at 85 K. Previous work 66,69 had shown that, at temperatures below 300 K, NO adsorbed molecularly and a c(4 × 2) LEED pattern was observed at the saturation coverage of 0.5 ML.…”
Section: No Surface Structurementioning
confidence: 99%
“…For the particular case of NO adsorption on Ni{111}, vibrational studies 29,30 suggested that NO was adsorbed in a 2-fold bridge site, and both bent and upright species were suggested as a function of coverage. However, diffraction based structural studies [31][32][33][34] showed that NO occupies 3-fold sites over the whole coverage range. Recent density functional theory (DFT) calculations 35,36 have also shown disagreement with conclusions from the earlier vibrational studies for NO adsorption on other surfaces.…”
Section: Introductionmentioning
confidence: 99%